Numerical model of metal-semiconductor contact - Асанов, Э.Э.; Зуев, С.А.; Килесса, Г.В.; Слипченко, Н.И. (Radiotekhnika, 2012)
The theoretical provisions are presented, the numerical model of ohmic contact metal semiconductor and Schottky barrier was constructed on their basis. Method of large particles is used in the model. The current- voltage characteristics are received as a result of the carried-out computing experiments.